2021
DOI: 10.1177/13506501211004313
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the mechanical durability of superamphiphobic surfaces: A review

Abstract: Superamphiphobic (water and oil repellent) surfaces have distinct application areas such as anti-corrosion, anti-friction, anti-icing, self-cleaning, etc. To fabricate these types of surfaces, the base material must have low surface energy and dual-scale roughness (micro and nano levels). The durability of such surfaces is indicated by the duration up to which they remain stable and effective. When mechanical forces interact with these surfaces, it deteriorates the surface integrity and ultimately degrades its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 200 publications
(241 reference statements)
0
6
0
Order By: Relevance
“…To experimentally achieve the wettability gradient, the surface properties need to be modified. There are many studies available in which the researchers use low surface energy materials like different polymers and ceramics, [48][49][50][51] diamond-like carbon (DLC), 52 and polyetheretherketone (PEEK). 53 These low surface energy materials have self-lubricating properties, which are useful in bearings, especially, in direct metal-to-metal contact.…”
Section: Introductionmentioning
confidence: 99%
“…To experimentally achieve the wettability gradient, the surface properties need to be modified. There are many studies available in which the researchers use low surface energy materials like different polymers and ceramics, [48][49][50][51] diamond-like carbon (DLC), 52 and polyetheretherketone (PEEK). 53 These low surface energy materials have self-lubricating properties, which are useful in bearings, especially, in direct metal-to-metal contact.…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental outcomes showed good agreement with the predicted simulation results. Singh et al [22] reported a review on the durability tests performed by various researchers on different slip/non-wettable polymer coatings. It was concluded that various low surface energy polymer coatings on the metallic substrate can resist frictional wear to a certain extent at lightly loaded conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These coatings are inspired by the unique wettability of plants and animals found in nature, such as lotus leaves [18], water striders' legs [19], rose petals [15], etc. The application of superhydrophobic coatings in oil-contaminated environments is restricted since these coatings, even with basic micro-and nano-rough structures, are frequently unable to repel oil and other liquids with a surface energy lower than water [20,21]. In order to expand the coating's wettability resistance from water to oil, the concept of superamphiphobic surfaces has emerged, i.e., the contact angle of both water and oil is greater than 150 • , and the sliding angle of both water and oil is less than 10 • [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Wang [35] claims that, compared to nano-spherical particles with rough surfaces, the coating made by the spraying method using smooth nano-spheres has much less liquid repellency. Cassie's principle [21] states that the solid-liquid contact area and contact angle decrease with increasing filler particle surface roughness. Consequently, employing the spraying method to create superamphiphobic coating microstructures might be aided by creating superamphiphobic filler particles with rough surfaces.…”
Section: Introductionmentioning
confidence: 99%